2013
DOI: 10.3346/jkms.2013.28.7.1077
|View full text |Cite
|
Sign up to set email alerts
|

Print Media Coverage of Post-Traumatic Stress Disorder: Content Analysis of Three Major Korean Newspapers

Abstract: The print media is still one of major sources for health-related information. To shed light on how the media accurately delivers information for post-traumatic stress disorder (PTSD), we searched the newspaper articles and analyzed their contents for accuracy in the description of symptoms, causes, and treatment of PTSD. The articles featuring PSTD were searched from the very first available to 2010 at on-line search systems of three major Korean newspapers. A total of 123 articles appeared and the first artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(44 reference statements)
0
11
1
Order By: Relevance
“…Research that explores representations of PTSD in the popular press would also be valuable to inform traumatic stress policy‐advocacy initiatives. A content analysis of stories about PTSD in major Korean newspapers, for example, found broad discrepancies in the accuracy of information that was presented (Jeong, Kim, Oh, & Park, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research that explores representations of PTSD in the popular press would also be valuable to inform traumatic stress policy‐advocacy initiatives. A content analysis of stories about PTSD in major Korean newspapers, for example, found broad discrepancies in the accuracy of information that was presented (Jeong, Kim, Oh, & Park, ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis of coverage of PTS in Korean newspapers found that only a quarter or the articles mentioned treatment. 'This is a substantial problem when the media is considered to be a source for health information and education for the public' (Jeong et al, 2013(Jeong et al, : 1080. This applies in our study as well.…”
Section: Discussion: Episodic Not Thematic Frames; Men Not Womenmentioning
confidence: 99%
“…Previous studies of media representation of PTS have found that, much like coverage of other health concerns, news reports usually focus on specific events, not the broader issue of PTS, and that focus, researchers say, shapes public understanding of trauma, treatment, and recovery. One study of news stories in Korean newspapers found the majority of articles analyzed focused on specific events; there was little information about causes of PTSD beyond that, leading researchers to conclude that articles blamed survivors for subsequent problems in coping with trauma (Jeong et al, 2013). A separate study of The New York Times , which analyzed articles from 1950 through 2012, also found a focus on events.…”
Section: Post-traumatic Stress: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as media increasingly draw attention to various issues regarding mental health problems and their contributions to social issues such as suicide, domestic abuse, and violent crime ( 18 ), the public perceptions of psychological/psychiatric disorders and their treatments are now changing. While depression and schizophrenia are amongst the most publicly well-known psychiatric disorders, it was not until recently that PTSD has been subjected to any kind of public discussion in Korea.…”
Section: Discussionmentioning
confidence: 99%